e e game

Calculus Level 3

e = ? \large e = ?

k = 0 ( k 1 ) 2 k ! \sum_{k=0}^\infty \dfrac{(k-1)^2}{k!} k = 1 2 k 2 3 k \sum_{k=1}^2\dfrac{k^2}{3k} None of these k = 0 ( 2 k + 3 ) 2 5 k ! \sum_{k=0}^\infty \dfrac{(2k+3)^2}{5k!}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Naren Bhandari
Oct 20, 2017

S 1 = k = 1 2 k 2 3 k = 1 3 k = 1 2 k = 1 \begin{aligned}S_1 & = \displaystyle\sum_{k=1}^{2}\frac{k^2}{3k}\\& = \frac{1}{3}\displaystyle\sum_{k=1}^{2}k \\& = \boxed{1}\end{aligned} S 2 = k = 0 ( k 1 ) 2 k ! = k = 0 k 2 2 k + 1 k ! = k = 0 k 2 k ! 2 k k ! + 1 k ! = k = 0 k ( k 1 ) ! 2 ( k 1 ) ! + 1 k ! = k = 0 k 1 + 1 ( k 1 ) ! 2 ( k 1 ) ! + 1 k ! = k = 0 k 1 ( k 1 ) ! + 1 ( k 1 ) ! 2 ( k 1 ) ! + 1 k ! = k = 0 1 ( k 2 ) ! 1 ( k 1 ) ! + 1 k ! = ( e e ) + k = 0 1 k ! = k = 0 1 k ! = e \begin{aligned} S_2 & = \displaystyle\sum_{k=0}^{\infty} \frac{(k-1)^2}{k!} \\ & = \displaystyle\sum_{k=0}^{\infty} \frac{k^2-2k+1}{k!} \\ & = \displaystyle\sum_{k=0}^{\infty} \frac{k^2}{k!}-\frac{2k}{k!}+\frac{1}{k!} \\& = \displaystyle\sum_{k=0}^{\infty} \frac{k}{(k-1)!}-\frac{2}{(k-1)!}+\frac{1}{k!} \\& = \displaystyle\sum_{k=0}^{\infty} \frac{k-1+1}{(k-1)! }-\frac{2}{(k-1)!}+\frac{1}{k!} \\&= \displaystyle\sum_{k=0}^{\infty}\frac{k-1}{(k-1)!}+\frac{1}{(k-1)!}-\frac{2}{(k-1)!}+\frac{1}{k!} \\& = \displaystyle\sum_{k=0}^{\infty}{\color{#D61F06}\frac{1}{(k-2)!}-\frac{1}{(k-1)!}}+\frac{1}{k!} = (e-e) +\displaystyle\sum_{k=0}^{\infty}\frac{1}{k!} \\& = \displaystyle\sum_{k=0}^{\infty} \frac{1}{k!} \\& = \boxed{e}\end{aligned} S 3 = k = 0 ( 2 k + 3 ) 2 5 k ! = 1 5 k = 0 4 k 2 + 12 k + 9 k ! = 1 5 k = 0 4 k 2 k ! + 12 k k ! + 9 k ! = 1 5 k = 0 4 k ( k 1 ) ! + 12 ( k 1 ) ! + 9 k ! = 1 5 k = 0 4 ( k + 1 ) ( k 2 ) ! + 12 ( k 1 ) ! + 9 k ! = 1 5 ( 4 ( 2 e ) + 12 e + 9 e ) = 29 e 5 \begin{aligned} S_3 & = \displaystyle\sum_{k=0}^{\infty} \frac{(2k+3)^2}{5k!} \\ & = \frac{1}{5}\displaystyle\sum_{k=0}^{\infty} \frac{4k^2+12k+9}{k!} \\ & = \frac{1}{5}\displaystyle\sum_{k=0}^{\infty} \frac{4k^2}{k!}+\frac{12k}{k!}+\frac{9}{k!} \\& = \frac{1}{5}\displaystyle\sum_{k=0}^{\infty} \frac{4k}{(k-1)!}+\frac{12}{(k-1)!}+\frac{9}{k!} \\& = \frac{1}{5}\displaystyle\sum_{k=0}^{\infty} \frac{4(k+1)}{(k-2)! }+\frac{12}{(k-1)!}+\frac{9}{k!} \\& =\frac{1}{5}(4(2e)+12e+9e) \\& = \boxed{\frac{29e}{5}}\end{aligned}

Why the red part cancels?

Alex Gómez Borrego - 3 years, 7 months ago

Log in to reply

I have extended the solution a bit for more clarifications. Hope it helps you. :)

Naren Bhandari - 3 years, 7 months ago
Chew-Seong Cheong
Oct 26, 2017

S 1 = k = 1 2 k 2 3 k = k = 1 2 k 3 = 1 3 + 2 3 = 1 e \begin{aligned} S_1 & = \sum_{k=1}^2 \frac {k^2}{3k} = \sum_{k=1}^2 \frac {k}{3} = \frac 13 + \frac 23 = 1 \color{#D61F06} \ne e \end{aligned}


S 2 = k = 0 ( k 1 ) 2 k ! = k = 0 k 2 2 k + 1 k ! = k = 0 k 2 k ! 2 k = 0 k k ! + k = 0 1 k ! = s 2 2 s 1 + s 0 \begin{aligned} S_2 & = \sum_{k=0}^\infty \frac {(k-1)^2}{k!} = \sum_{k=0}^\infty \frac {k^2-2k+1}{k!} = {\color{#3D99F6}\sum_{k=0}^\infty \frac {k^2}{k!}} - 2{\color{#D61F06} \sum_{k=0}^\infty \frac k{k!}} + \sum_{k=0}^\infty \frac 1{k!} = {\color{#3D99F6}s_2} - 2{\color{#D61F06}s_1} + s_0 \end{aligned}

  • s 0 = k = 0 1 k ! = e \begin{aligned} s_0 & = \sum_{k=0}^\infty \frac 1{k!} = e \end{aligned}
  • s 1 = k = 0 k k ! = k = 1 k k ! = k = 0 k + 1 ( k + 1 ) ! = k = 0 1 k ! = e \begin{aligned} s_1 & = \sum_{\color{#3D99F6}k=0}^\infty \frac k{k!} = \sum_{\color{#D61F06}k=1}^\infty \frac k{k!} = \sum_{\color{#3D99F6}k=0}^\infty \frac {k+1}{(k+1)!} = \sum_{\color{#3D99F6}k=0}^\infty \frac 1{k!} = e \end{aligned}
  • s 2 = k = 0 k 2 k ! = k = 1 k 2 k ! = k = 0 ( k + 1 ) 2 ( k + 1 ) ! = k = 0 k + 1 k ! = s 1 + s 0 = 2 e \begin{aligned} s_2 & = \sum_{\color{#3D99F6}k=0}^\infty \frac {k^2}{k!} = \sum_{\color{#D61F06}k=1}^\infty \frac {k^2}{k!} = \sum_{\color{#3D99F6}k=0}^\infty \frac {(k+1)^2}{(k+1)!} = \sum_{\color{#3D99F6}k=0}^\infty \frac {k+1}{k!} = s_1+s_0 = 2e \end{aligned}

S 2 = s 2 2 s 1 + s 0 = 2 e 2 e + e = e \implies S_2 = s_2-2s_1+s_0 = 2e-2e+e\color{#3D99F6} = e . Therefore, the answer is k = 0 ( k 1 ) 2 k ! \boxed{\displaystyle \sum_{k=0}^\infty \frac {(k-1)^2}{k!}} .


S 3 = k = 0 ( 2 k + 3 ) 2 5 k ! = k = 0 4 k 2 + 12 k + 9 5 k ! = 4 s 2 + 12 s 1 + 9 s 0 5 = 8 + 12 + 9 5 e = 29 5 e e \begin{aligned} S_3 & = \sum_{k=0}^\infty \frac {(2k+3)^2}{5k!} = \sum_{k=0}^\infty \frac {4k^2+12k+9}{5k!} = \frac {4s_2+12s_1+9s_0}5 = \frac {8+12+9}5e = \frac {29}5 e \color{#D61F06} \ne e \end{aligned}


Generalisation: s n = k = 0 n 1 ( n 1 k ) s k \displaystyle s_n = \sum_{k=0}^{n-1} {n-1 \choose k} s_k

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...